Early neonatal outcomes of very-low-birth-weight infants in Turkey: A prospective multicenter study of the Turkish Neonatal Society - MEMİŞOĞLU, ASLI (My University, 2019)
Objective
Keywords: Temel Bilimler; Natural Sciences; ÇOK DİSİPLİNLİ BİLİMLER; Doğa Bilimleri Genel; Temel Bilimler (SCI); MULTIDISCIPLINARY SCIENCES; NATURAL SCIENCES, GENERAL; Natural Sciences (SCI); Multidisipliner; Multidisciplinary